(untitled) (Journal of actual problems of jurisprudence, 2021)
The category «security» reflects the key aspects of human being and consciousness, as well as the function created by people of higher social systems – society and state. The conflicts observed in the modern world are due to the clash of two leading ideological concepts in the security policy of states – realism and liberalism, which in various forms is also transferred to the individual and public consciousness. The aim of the study is to attempt to generalize existing knowledge about realism and realism. This should contribute to a deep and holistic understanding of the person’s current events, the development of his worldview and political culture in the security sphere. The article analyzes the genesis of the main ideas of realism and liberalism, their current state and development tendencies. As the results of the study, the most important differences and similarities of the corresponding concept are presented, and they are disclosed to be suitable for their synthesis in the science and practice of state construction. The conclusion is made that Kazakhstan realizes the solution of internal policy issues on the basis of the ideas of classical liberalism, and in outer one – the main vector is the neorealistic paradigm. The article is prepared within the framework of the grant scientific project «Methodological foundations of national security of the Republic of Kazakhstan: a systematic approach» (АР05136053). Key words: realism, liberalism, security policy.